Sensitivity Analysis for Convex Multiobjective Programming in Abstract Spaces - Balbás, A.; Guerra, P.Jiménez (Journal of mathematical analysis and applications, 1996)
The main object of this paper is to prove that for a linear or convex multiobjective program, a dual program can be obtained which gives the primal sensitivity without any special hypothesis about the way of choosing the optimal solution in the efficient set.